Traumatic dislocation of the lumbosacral joint in two cats - Zulauf, D.; Koch, D.; Voss, K. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
The clinical and radiological features, surgical treatment, and outcome of two cats with traumatically induced dislocation of the lumbosacral joint are described in this report. The dislocation of the lumbosacral joint was concurrent with dorsal luxation of the articular facets in both cases. Open reduction, followed by stabilization with a dorsal suture sling, resulted in a good clinical outcome.
Keywords: Lumbosacral; dislocation; luxation; cat